Performance of pre and post-emergence herbicides in Bt-cotton crop - Singh, Harpreet; Manhas, S.S. (Annals of Agricultural Research, 2016)
A field experiment was carried out at Bathinda during kharif- 2013 to study the performance of preand post-emergence herbicides in Bt-cotton crop. The experiment was laid out in randomized blockdesign with 8 treatments and 3 replications. Results revealed that all herbicides either applied aloneor in combination significantly reduced the weed population and dry matter accumulation incomparison to weedy check. Application of Pyrithiobac Sodium @ 62.5 g/ha followed byQuizalofopethyl 50 g/ha both at 2-4 weed leaf stage + One Hoeing at 40-60 days after sowing (DAS)significantly reduced weed population and dry matter accumulation as compared to other treatments.The maximum growth parameters, yield attribute and yield were recorded with the application ofPyrithiobac Sodium @ 62.5 g/ha followed by Quizalofopethyl 50 g/ha both at 2-4 weed leaf stage +One Hoeing at 40-60 DAS which was at par with Pendimethalin @ 1000 g/ha + Quizalofopethyl @50 g/ha at 2-4 weed leaf stage + One Hoeing at 40-60 DAS and significantly higher than othertreatments of weed control.Net monetary returns (103403 Rs/ha) and benefit cost ratio (2.30) wasobserved with Pyrithiobac Sodium @ 62.5 g/ha followed by Quizalofopethyl 50 g/ha both at 2-4weed leaf stage + One Hoeing at 40-60 DAS which was at par with Pendimethalin @ 1000 g/ha +Quizalofopethyl @ 50 g/ha at 2-4 weed leaf stage + One Hoeing at 40-60 DAS and significantlyhigher than other treatments of weed control.